2010
DOI: 10.1073/pnas.1018224108
|View full text |Cite
|
Sign up to set email alerts
|

Immature T-cell clustering and efficient differentiation require the polarity protein Scribble

Abstract: T-cell polarization is required for cell migration and cell-cell interactions, cellular behaviors crucial for lymphocyte differentiation. Despite expression of the epithelial polarity network in T cells, neither its contribution to thymocyte polarity nor its requirement during development is known. We report here that depletion of the polarity protein Scribble in hematopoietic progenitor cells results in inefficient T-cell development characterized by a partial developmental block during the early double-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Indeed, several studies linked Scrib to migratory processes in epithelial cells, fibroblasts, and lymphocytes. 20 There is, however, little consensus on the specific role and functions of Scrib during migration, and its localization reportedly varies between cells and assay systems used. In epithelial Madin Darby canine kidney (MDCK) cells, Scrib downregulation induces cell migration in Boyden chamber experiments, 16 whereas in breast carcinoma cells (T47D, MCF10A) and fibroblasts Scrib downregulation reduced cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies linked Scrib to migratory processes in epithelial cells, fibroblasts, and lymphocytes. 20 There is, however, little consensus on the specific role and functions of Scrib during migration, and its localization reportedly varies between cells and assay systems used. In epithelial Madin Darby canine kidney (MDCK) cells, Scrib downregulation induces cell migration in Boyden chamber experiments, 16 whereas in breast carcinoma cells (T47D, MCF10A) and fibroblasts Scrib downregulation reduced cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…As others before, we observed that T cell aggregation depended on ERK1/2 signaling (22,49), as the addition of an inhibitor of ERK1/2 signaling abrogated the formation of large aggregates. T cell aggregation has been described to correlate with T cell migration (43,44). Other viruses, like human T cell lymphotropic virus type 1 (HTLV-1) and the betaherpesvirus human cytomegalovirus (HCMV), trigger migration of virus-inoculated leukocytes (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…T cell aggregation is often associated with increased cellular motility (43,44). We therefore assessed whether PRV gE triggers T cell migration.…”
Section: Addition Of Recombinant Ge To Jurkat T Cells Leads To Rapidmentioning
confidence: 99%
“…Scribble inhibition in fetal liver progenitor cells results in a partial block during DN3 progression. 37 Down-regulation of Ptcra and Scrib correlates with the delayed DN23DN3 progression and could contribute to the increased proportion of ETP/DN2 thymocytes observed in the presence of Wnt4 in vivo and in vitro. In various cell types, Wnt4 can elicit canonical, noncanonical, or both types of Wnt signaling.…”
Section: Wnt4 In Fetal and Postnatal Thymopoiesis 5167mentioning
confidence: 99%